Microbial activity in the gut of piglets: effect of prebiotic and probiotic supplementation - Lordelo, M.M. (2009)
Four groups of six 21 days-old piglets were used to evaluate the effect of a prebiotic or probiotic on the intestinal fermentative activity. In each group, piglets received one of the following diets: basal diet (C); basal diet supplemented with xylooligosaccharide (C-XOS); basal diet supplemented with Saccharomyces cerevisiae (C-SC); and basal diet supplemented with xylooligosaccharide and S. cerevisiae (C-XOS+SC). The short chain fatty acids in the colon of piglets were decreased with the inclusion of S. cerevisiae in the diet (Pb0.01). The xylanolytic activity was higher (Pb0.05) in the small intestine of piglets fed C-XOS+SC diet, but no significant differences were found in the caecum and colon. In the caecum contents, the cellulolytic activity was increased (Pb0.05) by the C-XOS and C-SC diets, but remained similar when the diet was supplemented with the two additives combined.